Qisas Dalam Islam Dan Relevansinya Dengan Masa Kini - Darussamin, Zikri (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2014)
Qi???in the terminology of Islamic law is a retaliation applied in cases of killing (qi??? f? an-nafs) and of uncritical wounding (qi??? f? m? d?n annafs). Is it now relevance or not to exercise qi???in order to prevent such cases? Nowadays, the debate on this issue continues to flourish, which is apparently hard to concur for those who involve in this debate stand on two different grounds, namely religious belief vs humanistic perspective. Be that as it may, one cannot deny the fact that while qi?h??constitutes one of Islamic doctrines that every moslem uphold, the application of qi?h??itself seems to have greater effects on the society with which they can maintain proper human rights.